Effect of cutting edge geometry change due to tool wear on hole quality in drilling of carbon fiber reinforced plastics using advanced ceramic coated tools. (January 2022) - Bin Abdullah, Mohammad Sayem; Kim, Dave; Kwon, Patrick; Kim, Tae-Gon
This paper aims to study the evolution of cutting edge geometry due to tool wear and discuss its impact on the hole quality of a carbon fiber reinforced plastic (CFRP) laminate. A drilling experiment was conducted using three types of twist drills: uncoated, BAM (AlMgB14 ) coated, and (AlCrSi/Ti)N nanocomposite coated tungsten carbide tools. After generating 120 holes, the uncoated drill had the largest cutting edge radius (∼36 µm), while the BAM coated drill had the most extensive flank wear (∼287 µm) among the three drills. This relatively rapid tool wear results in a reduction of average hole size and a considerable variation on the hole profiles. The worn drills with the cutting edge radius greater than 19.3 µm form the fiber pull-outs in not only the 135° plies but also the adjacent 45° and 90° plies from the cutting direction, creating deep void networks. This type of networked fiber pull-out damage was observed with the holes machined by the uncoated and BAM coated drills. The (AlCrSi/Ti)N coated drill, which experienced the least amount of flank wear and the least increase of cutting edge radius, generated consistently sized holes up to 120 holes. However, the relatively sharp (AlCrSi/Ti)N coated tool results in the higher arithmetic roughness average (Ra) and the maximum roughness height (Rz) values than the other tools due to the localized fiber pull-outs and the absence of severe matrix smearing.